Analysis of Common Ethical Review Issues in Biomedical Research in Medical Universities - Hui JIANG; Huixian HUANG; Min CHEN (Yixue yu zhexue, 2025)
This paper conducts an in-depth analysis of the issues existing in the ethical review of biomedical research in medical universities, covering various aspects such as the scientific validity of research design, the standardization of informed consent, the feasibility of research teams, the compliance of application reviews, the legality of registration management, and the fairness of research outcome sharing. By sorting out these issues, the paper proposes targeted improvement measures, including enhancing ethical awareness, implementing management responsibilities, perfecting the ethical review process, and accepting public oversight. Additionally, the article emphasizes that medical scientific activities should strictly adhere to international ethical standards to promote the development of ethical governance and social progress in China, ensuring the healthy advancement of biomedical research.